Metabolism of Uridine 5′-Diphosphate-Glucose in Golgi Vesicles from Pea Stems - Neckelmann, Guy (American Society of Plant Physiologists, 1998)
Uridine 5′-diphosphate-glucose (UDP-Glc) is transported into the lumen of the Golgi cisternae, where is used for polysaccharide biosynthesis. When Golgi vesicles were incubated with UDP-[(3)H]Glc, [(3)H]Glc was rapidly transferred to endogenous acceptors and UDP-Glc was undetectable in Golgi vesicles. This result indicated that a uridine-containing nucleotide was rapidly formed in the Golgi vesicles. Since little is known about the fate of the nucleotide derived from UDP-Glc, we analyzed the metabolism of the nucleotide moiety of UDP-Glc by incubating Golgi vesicles with [α-(32)P]UDP-Glc, [β-(32)P]UDP-Glc, and [(3)H]UDP-Glc and identifying the resulting products. After incubation of Golgi vesicles with these radiolabeled substrates we could detect only uridine 5′-monophosphate (UMP) and inorganic phosphate (Pi). UDP could not be detected, suggesting a rapid hydrolysis of UDP by the Golgi UDPase. The by-products of UDP hydrolysis, UMP and Pi, did not accumulate in the lumen, indicating that they were able to exit the Golgi lumen. The exit of UMP was stimulated by UDP-Glc, suggesting the presence of a putative UDP-Glc/UMP antiporter in the Golgi membrane. However, the exit of Pi was not stimulated by UDP-Glc, suggesting that the exit of Pi occurs via an independent membrane transporter.